NILAI-NILAI SOSIAL DAN BUDAYA PADA TRADISI SEA NONO HEU DALAM MASYARAKAT AMARASI - Pasriani Damayanti Akunut; Hiwa Wonda (STKIP Subang, 2025)
This study examines the Sea Nono Heu tradition, a traditional ceremony that holds significant significance in the marriage system of the Amarasi people on Timor Island, East Nusa Tenggara. This tradition is part of a series of customary wedding ceremonies that must be carried out as a symbol of a woman's transition from her native clan to her husband's clan. This study used literature study and interview methods to explore the meaning, values, and implementation process of Sea Nono Heu. The results show that this tradition not only serves a social function as a marker of a woman's transition in status, but also has high spiritual and symbolic value. Through this ritual, the Amarasi people emphasize the patrilineal kinship system and respect for ancestors. The implementation process involves a series of traditional symbols, such as the draping of a shawl around the neck and the prohibition of looking back for the bride, which represent the change of clan and readiness to start a new life in the husband's family. Thus, Sea Nono Heu is not just a traditional wedding procession, but a reflection of the values ​​of togetherness, respect, and preservation of the Amarasi people's cultural identity that have been passed down from generation to generation.